A proton exchange membrane fuel cell-compound thermoelectric system: Bidirectional modeling and energy conversion potentials. (1st March 2020) - Cai, Yang; Wang, Wei-Wei; Wang, Lei; Liu, Di; Zhao, Fu-Yun
Highlights: Energy, exergy and exergoeconomic analyses of the FC-TEH system were performed. Parametric comparison between FC-TEC and FC-TEG modes was thoroughly conducted. Irreversibilities were evaluated in terms of exergy destruction factor and efficiency. Operating regimes of thermoelectric models in FC-TEH system were clearly revealed. Thermoelectric conversion could be a key for fully exploiting energy potential. Abstract: Thermoelectric device may appear as thermoelectric cooling (TEC) mode or thermoelectric generation (TEG) mode when it is generally applied to recover the waste heat produced from proton exchange membrane fuel cell (PEMFC), typically operating in the range of 60–80 °C. Although PEMFC integrated thermoelectric cooler or generator has been investigated separately in the past years, researches regarding their simultaneous TEC and TEG modes are still not reported so far. In the present work, a comprehensive thermodynamic performance analysis of the fuel cell-thermoelectric hybrid (FC-TEH) system considering TEC and TEG models simultaneously is conducted to exploit the energy conversion potential of the electrochemical and thermoelectric coupling processes. Irreversible characteristics and exergoeconomic performance of the hybrid system are thoroughly analyzed through combining finite time thermodynamics and thermodynamic economics. Subsequently, parametric comparisons between the fuel cell-thermoelectric cooling (FC-TEC) and the fuel cell-thermoelectric generation (FC-TEG) models are sensitively identified in terms of the decision targets, such as power output, energy efficiency, exergy efficiency and unit exergy cost. In addition, operating regimes of thermoelectric models in FC-TEH system are further determined to reveal thermoelectric conversion conditions and ensure efficient operation of the thermoelectric device (TED). Present results further demonstrate that FC-TEH system firstly behaves as FC-TEC in the current density range of 0–1.2 A/cm 2, then FC-TEG and ultimately FC-TEC mode; where, only the TEG mode has the positive influence on the power output of the hybrid system. In addition, effective ranges of current density for the FC-TEG mode and minimum unit exergy cost are also confirmed. Present research may be significant for fully enhancing the energy and exergy performance of electrochemical – thermoelectric process.